2019
DOI: 10.1002/pon.4975
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty, social support, and loneliness in relation to anxiety and depressive symptoms among women diagnosed with ovarian cancer

Abstract: Objective Intolerance of uncertainty (IU) is a trait variable that captures an individual's lack of tolerance for unknown outcomes and events. Positive correlations between IU and mental health symptoms have been observed in various populations, while social variables (social support and decreased loneliness) seem to serve as protective factors against psychological distress among individuals with cancer. The present study examined the moderation effect of social support and loneliness in the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 40 publications
3
40
0
2
Order By: Relevance
“…Our results are in line with previous studies about these themes (Sadler and Weiss, 1975;Simard et al, 2013). The relevance of loneliness as a contributor to mental health is confirmed by previous studies showing its predictive role in the development and maintenance of depressive and anxiety symptoms (Wang et al, 2018;Hill and Hamm, 2019). Moreover, loneliness has been found to have impact on other chronic and various diseases: for example, cognitive decline (Shankar et al, 2013), cardiovascular diseases (Herlitz et al, 1998;Sorkin et al, 2002;Hawkley et al, 2010), cancer (Antoni et al, 2006), and inflammatory diseases (Luanaigh and Lawlor, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with previous studies about these themes (Sadler and Weiss, 1975;Simard et al, 2013). The relevance of loneliness as a contributor to mental health is confirmed by previous studies showing its predictive role in the development and maintenance of depressive and anxiety symptoms (Wang et al, 2018;Hill and Hamm, 2019). Moreover, loneliness has been found to have impact on other chronic and various diseases: for example, cognitive decline (Shankar et al, 2013), cardiovascular diseases (Herlitz et al, 1998;Sorkin et al, 2002;Hawkley et al, 2010), cancer (Antoni et al, 2006), and inflammatory diseases (Luanaigh and Lawlor, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…The significant psychological impact on oncological patients is compounded by multiple factors during the pandemic -knowledge that the individual is at higher risk of serious complication if infected by Covid-19, loneliness and isolation as a result of social distancing, and the underlying constant fear of the cancer. Loneliness is associated with higher risk of mortality in cancer patients 34,35 . Social distancing is known to have negative health consequences and increase risk for premature mortality during normal times 36 , but it also enhances patients' feelings of uncertainty associated with their prognosis.…”
Section: The Psychological Management Of Cancer Patients During the Cmentioning
confidence: 99%
“…IU was regarded as an important factor to influence public mental health [17,18]. Numerous researches showed that generalized anxiety, depression, or other mental health problems were significantly associated with IU among a broad range of samples [16], such as mothers of children with autism spectrum disorder [19], public safety personnel [20], women diagnosed with ovarian cancer [21], pregnant women [22], and men on active surveillance for prostate cancer [23]. Furthermore, a high level of IU scores implicated serious psychological problems [16].…”
Section: Intolerance Of Uncertainty and Mental Healthmentioning
confidence: 99%